Chronic symptoms in patients with unilateral vestibular hypofunction: systematic review and meta-analysis - Karabulut, Mustafa; Van Laer, Lien; Hallemans, Ann; Vereeck, Luc; Van Rompaey, Vincent; Viechtbauer, Wolfgang; Melliti, Ali; van Stiphout, Lisa; Mohamad, Alfarghal; Pérez Fornos, Angélica; Guinand, Nils; van de Berg, Raymond (Frontiers in Neurology, 2023)
Objective:To systematically evaluate the full spectrum of self-reported chronic symptoms in patients with unilateral vestibular hypofunction (UVH) and to investigate the effect of interventions on these symptoms.Methods:A literature search was performed in Pubmed, Web of Science, Embase, and Scopus to investigate self-reported symptoms and self-report questionnaires in patients with UVH. All original studies ranging from full-text clinical trials to case reports, written in English, German, and French, were included. The frequency of self-reported symptoms was presented. For self-report questionnaires, a meta-analysis was carried out to synthesize scale means by the pre-and post-intervention means and mean changes for studies that investigated interventions.Results: A total of 2110 studies were retrieved. Forty-seven studies were included after title-abstract selection and full-text selection by two independent reviewers. The symptoms of UVH patients included chronic dizziness (98%), imbalance (81%), symptoms worsened by head movements (75%), visually induced dizziness (61%), symptoms worsened in darkness (51%), and oscillopsia (22%).Regarding self-report questionnaires, UVH resulted on average in a moderate handicap, with an estimated mean total score on the Dizziness Handicap Inventory (DHI) and the Vertigo Symptom Scale (VSS) of 46.31 (95% CI: 41.17-51.44) and 15.50 (95% CI: 12.59-18.41), respectively. In studies that investigated the effect of vestibular intervention, a significant decrease in the estimated mean total DHI scores from 51.79 (95% CI: 46.61-56.97) (pre-intervention) to 27.39 (95% CI: 23.16-31.62) (post intervention) was found (p<.0001). In three studies, the estimated mean total Visual Analog Scale (VAS) scores were 7.05 (95% CI: 5.64-8.46) (pre-intervention) and 2.56 (95% CI: 1.15-3.97) (post-intervention). Finally, a subgroup of patients (>32%) persists with at least a moderate handicap, despite vestibular rehabilitation.A spectrum of symptoms is associated with UVH, of which chronic dizziness and imbalance are most frequently reported. However, semi-structured interviews should be conducted to define the whole spectrum of UVH symptoms more precisely, in order to establish a validated patient-reported outcome measure (PROM) for UVH patients. Furthermore, vestibular interventions can significantly decrease self-reported handicap, although this is insufficient for a subgroup of patients. It could therefore be considered for this subgroup of patients to explore new intervention strategies like vibrotactile feedback or the vestibular implant.